PWE-132 A re-evaluation of epidemiology and resistance patterns of culture-positive spontaneous bacterial peritonitis in leeds. (22nd June 2015) - Harrison, L; Sandoe, J; Aldersley, M; Jennings, J
Abstract : Introduction: Spontaneous bacterial peritonitis (SBP) is a frequent and serious condition with significant morbidity and mortality in patients with liver cirrhosis. Early diagnosis and prompt treatment of SBP reduces in-hospital mortality from 90% to <20%. 1 As a result of an audit of SBP in 2006–2008, first line antibiotic for treatment was changed to piperacillin/tazobactam and cotrimoxazole was recommended for secondary prophylaxis. The outcome of these changes was evaluated. Method: A retrospective microbiology database search was carried out on fluid samples in Leeds, a teaching hospital with liver transplantation services. The samples were obtained between December 2008 and October 2014, grew a single organism, and had an ascitic fluid neutrophil count of ≥0.25 × 10 9 /L. Case notes were reviewed to establish a diagnosis of SBP. Resistance patterns were compared to samples received 2006–2008. Results: Of 2679 samples, 43 met criteria for single organism SBP. The mean age was 53.1 and 30/43 (70%) were men. Nine patients were Child's Pugh Score B and 34 were Child's Pugh Score C with a 30 day mortality of 22.2% and 56% respectively. The 30 day mortality was 48.8% (21/43) consistent with data from 2006–2008 audit. 74.4% patients had underlying alcohol related liver disease. 78.8% of organisms were Gram-negative with the majority being E coli . There was a large proportion of Gram-positive organisms which were mostly streptococci. Nine patients had prior SBP infections and twelve patients were prescribed secondary prophylaxis. Conclusion: SBP remains a poor prognostic indicator with a 48.8%, 30-day mortality. A high index of suspicion is essential and empirical antibiotic therapy should be provided. Our results demonstrate a shift from Gram-negative to Gram-positive organisms. This is likely to be due to previous exposure to antibiotics and secondary prophylaxis. Nationally there is an increase in multidrug-resistant Gram-negative organisms. Prior to 2010, quinolone antibiotics such as ciprofloxacin and cephalosporins were more widely used and recommended by BSG guidelines. This reaudit demonstrates a reduction in resistant organisms, especially to ciprofloxaxin. This demonstrates the importance of auditing and reviewing local antimicrobial guidelines. Disclosure of interest: None Declared. Reference: Garcia-Tsao G. Current management of the complications of cirrhosis and portal hypertension: variceal haemorrhage, ascites and spontaneous bacterial peritonitis. Gastroenterology. 2001;120:726-48